Are taxes to sugar-sweetened beverages and non-essential energy dense food implemented in Mexico regressive? - J Alai Quiroz-Reyes; Jesús Enrique Morales-Ríos; Adriana Vargas-Flores; Néstor A Sánchez-Ortiz; M Arantxa Colchero (PLoS ONE)
Introduction In January 2014, Mexico introduced an excise tax of $1.00 Mexican peso/liter on sugar-sweetened beverages (SSB) and an 8% tax on non-essential energy dense food (NEDF) with at least 275 kilocalories/100 grams. Fiscal policies could be regressive when taxes generate a greater financial burden for low-income households compared to higher-income households. The objective of this study was to analyze whether SSB and NEDF taxes in Mexico were regressive using a nationally representative survey. Materials and methods Information from the National Household Income and Expenditure Survey in Mexico in its 2014, 2016 and 2018 waves were used to estimate changes in expenditures on SSB and NEDF over total expenditures by income quintile and place of residence using own price elasticities, changes in prices after tax implementation and tax pass-through prices. We derived uncompensated own price elasticities using the Linear Approximation of the Almost Ideal Demand System. Results Price elasticities -in absolute values- were higher in urban areas than in rural settings for SSB in 2014 and 2016, while the opposite was observed for NEDF. For SSB, price elasticities -in absolute values- among households in the highest income quintiles were lower than those in the lowest income quintiles. The tax paid for SSB and NEDF over total expenditures was higher among low-income households. However, the reduction in SSB expenditures over total expenditures in low-income households was higher compared to the highest income quintile. For NEDF, weekly expenditures in rural areas were lower than in urban areas for the lowest quintile, while for the highest quintile the reduction was similar. Conclusions Low-income households in urban and rural areas reduced the proportion spent on SSB and NEDF more compared to higher-income residents, counteracting the regressive burden of the taxes.